Description Of The Level Of Knowledge Of Hypertensive Patients About Hypertension At Sukodono Community Health Center, Sidoarjo Regency - Zulfa Afidah Fitri Ana; Dony Sulystiono; Siti Maimuna; Alfi Maziyah (Prodi keperawatan sidoarjo, politeknik kesehatan kemenkes surabaya indonesia, 2025)
High blood pressure, often known as hypertension, is a common medical issue that can lead to major problems like stroke and cardiovascular diseases. Unhealthy lifestyle choices and a lack of knowledge about hypertension among those who are afflicted are typically linked to the start of the ailment. The research design used in this study was descriptive. A total of 84 respondents diagnosed with hypertension in the working area of Sukodono Public Health Center were recruited using a cross-sectional approach. The frequency distribution revealed that, among the 84 participants, knowledge of hypertension was categorized as good in 30 individuals (35.7%), moderate in 33 individuals (39.2%), and poor in 21 individuals (25.0%). Based on the findings, it can be concluded that the level of knowledge among hypertensive patients at Sukodono Public Health Center, Sidoarjo District, was predominantly at a moderate level, represented by 33 participants. The majority of these patients were between 51–60 years old, female, unemployed or housewives, and had attained a senior high school level of education. Accordingly, it is recommended that Sukodono Public Health Center strengthen its health education programs for hypertensive patients in order to enhance their understanding of the disease and to reduce the risk of more severe complications